Analisis Hanyutnya Cafe Xakapa Akibat Banjir Bandang di Lembah Anai Berbasis Sistem Informasi Geografis (GIS) - Montika, Fanni (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
Analysis of the Swept Away of Cafe Xakapa Due to Flash Floods in the Anai Valley Based on Geographic Information Systems (GIS) Café Xakapa is located right on the border of the Batang Anai River. The building in the form of a cafe, which was built for commercial purposes, offers a view of the Anai Valley Waterfall which is right on the side of Jalan Lintas Barat Sumatra. Tshe aim of this research is to determine the causes of flooding in the Anai Valley using several existing parameters. Apart from that, we also know the legality of the Café Xakapa building which was built in the Anai Valley River Watershed (DAS). Furthermore, you can determine appropriate disaster mitigation methods if the same natural disaster occurs as before. Researchers used descriptive qualitative research using the case study method. Case studies were chosen because researchers wanted to analyze the events behind the existing phenomena. The research results showed that Café Xakapa did not comply with PP Number 28 of 2015 concerning the Determination of River Boundary Lines. Then, rainfall is the main factor in flooding in addition to several other factors discussed. Café Xakapa was also built not in accordance with the applicable Regional Spatial Plan.